New Trends and Most Promising Therapeutic Strategies for Epilepsy Treatment - Riva, Antonella; Golda, Alice; Balagura, Ganna; Amadori, Elisabetta; Vari, Maria Stella; Piccolo, Gianluca; Iacomino, Michele; Lattanzi, Simona; Salpietro, Vincenzo; Minetti, Carlo; Striano, Pasquale (Frontiers in Neurology, 2021)
Background: Despite the wide availability of novel anti-seizure medications, thirty percent of patients with epilepsy retain persistent seizures with a significant burden in comorbidity and an increased risk of premature death. This review aims to discuss the therapeutic strategies, both pharmacological and non, which are currently in the pipeline. Methods: PubMed, Scopus, and EMBASE databases were screened for experimental and clinical studies, meta-analysis, and structured reviews published between January 2018 and September 2021. The terms ‘epilepsy’, ‘treatment’ or ‘therapy’ and ‘novel’ were used to filter the results. Conclusions: The common feature linking all the novel therapeutic approaches is the spasmodic rush towards precision medicine, aiming at holistically evaluating patients and treating them accordingly as a whole. Toward this goal, different forms of intervention may be embraced, starting from the choice of the most suitable drug according to one’s type of epilepsy or expected adverse effects, to the outstanding field of gene therapy. Moreover, innovative insights come from in-vitro and in-vivo studies on the role of inflammation and stem cells in the brain. Further studies on both efficacy and safety are needed, with the challenge to mature evidence into reliable assets, ameliorating patients’ symptoms, and answering the challenges of this disease.